The Contribution of Emotional Intelligence to The Training Motivation of 12 – 14 Years Old Adolescent Table Tennis Athletes in PTM Bandung District - Nurfairuz, Hasna Siti; Subroto, Toto; Gumilar, Agus (JUMORA: Jurnal Moderasi Olahraga, 2025)
This study's objective was to find and analyze the contribution of the impact of emotional intelligence, to training motivation and its impact on the achievement of table tennis athletes. The author uses a quantitative descriptive method. Utilizing a survey approach, quantitative research is the research methodology employed with an instrument using a questionnaire with a list of statements that have been structured with the aim of collecting information from emotional factors that affect the achievement of table tennis athletes as respondents in the study. The data was tested with a simple linear regression test to see the contribution between the emotional intelligence variable as the independent variable and training motivation as the dependent variable. The information description from the survey analysis of 51 respondents obtained the mean value of the emotional intelligence variable is 54.78 with a standard deviation of 6.74, while the training motivation variable is 56.24 with a standard deviation of 5.21. Regression analysis in table 2 shows the relationship or correlation coefficient (R) of 0.651. Based on the results results, The impact of the independent variable (emotional intelligence) on the dependent variable is indicated by the coefficient of determination (R Square), which is 0.424 (training motivation) is around 42.4%. This research reveals the importance of having emotional stability when performing physical activities and sports, which affects performance, response to stress, and psychological well-being. The emotional intelligence model consisting of knowledge, skills and attitudes provides a comprehensive framework for understanding emotional intelligence in sport. The model also highlights the positive relationship between emotional intelligence and subjective performance in sport. The research also highlights the importance of multi-sphere training in regulating energy, moisture and micronutrients, such as zinc, magnesium and vitamin D, in sports performance